A Callovian (Middle Jurassic) poriferan fauna from northwestern Jordan: taxonomy, palaeoecology and palaeobiogeography. (4th July 2018) - Ungureanu, Daniel; Ahmad, Fayez; Farouk, Sherif
Abstract: The present work describes the first fossil sponge assemblage from Jordan, belonging to Demospongiae and Calcarea; hexactinellid sponges are absent from the collections. Mughanniyyum hanium gen nov., sp. nov. is described, and a new subfamily, Jordaniinae, is proposed, belonging to Scleritodermatidae (Demospongiae). Another new demosponge species, Geoditesia jordaniensis sp. nov., is described on the basis of well-preserved specimens. The genus Geoditesia is previously known only from loose Geodia -type spicules. It is the first description of an articulated sponge bearing this kind of spicule. The assemblage is compared with similar occurrences in the Negev Desert (Israel) and Kachchh Basin (India). While the sponge fauna and the facies represented by the Negev Desert assemblage are very different, in the Kachchh Basin there are sponges present with similar external morphology belonging to related taxonomic groups. The palaeobathymetry of the studied sections from Jordan indicates slightly shallower water than in the Kachchh Basin. There is also slight stratigraphic difference between Jordan and the Indian Basin, in that the Jordanian assemblage is of Callovian age, while in Kachchh it is Bathonian.urn:lsid:zoobank.org:pub:6ED83BB8-E199-47B5-9A11-7B03E2C449F4